ENGLISH FOR TEENS : UPAYA MENINGKATKAN KESADARAN ANGGOTA KARANG TARUNA UNTUK MEMAHAMI DAN MEMPRAKTEKKAN BAHASA INGGRIS DALAM BERKOMUNIKASI - Ratna Kartika Sari (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2022)
Understanding and using English in communicating has become a necessity for everyone who wants to win the increasingly fierce competition in work and business in the era of globalization. However, there are still many people who have not realized and prepared themselves to learn English. The ease of accessing English learning materials in the current digital era is not used to improve communication skills. English For Teens, a training to communicate in English, was held with the aim of building and raising awareness of the younger generation so that they are motivated to learn and practice English. This qualitative research focuses on the problems faced by the managers of Karang Taruna RW.02 Bambu Apus, East Jakarta, and provides the best solution in building and increasing the awareness of its members to learn and practice English. Low understanding of English causes difficulties in communicating and accessing various information that is important for personal and organizational progress. English For Teens also tries to provide learning materials that are simple, varied, but easy to understand so as to eliminate the impression that learning English is very difficult and boring. The results of the training showed that the participants easily understood the learning material provided and could do the exercises. However, the main problem is when doing speaking, especially in how to pronounce words (pronunciation), so the tutor has to give examples of correct pronunciation over and over again.